Ultrasound Elastography 2020
DOI: 10.5772/intechopen.88183
|View full text |Cite
|
Sign up to set email alerts
|

2D Shear Wave Elastography for Liver Fibrosis Evaluation

Abstract: 2D shear wave elastography is a technique embedded in ultrasound machines which allows the interrogation of the tissue by acoustic radiation force impulses induced into the tissues by focused ultrasonic beams and captures the propagation of resulting shear waves in real time. Elasticity is displayed using a color-coded image superimposed on a B-mode image, and at the same time, a quantitative estimation of liver stiffness (LS) can be performed in a certain region of interest (ROI). The published data showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These studies have variable findings on the accuracy of SWE; however, its specificity and sensitivity are comparable to liver biopsy. Another study also found out that shear wave elastography is a reliable noninvasive modality for assessing liver elasticity (Popescu et al, 2019). In a study conducted on HBV patients for assessing the diagnostic value of SWE and liver biopsy, mean liver stiffness in F1, F2, F3, and F4 stage was 6.70 ± 2.65 kPa, 7.34 ± 3.84 kPa, 8.82 ± 3.24 kPa and 12.88 ± 5.25 kPa respectively (Kim and El-Serag, 2019), this was inline with the results of our study.…”
Section: Resultsmentioning
confidence: 94%
“…These studies have variable findings on the accuracy of SWE; however, its specificity and sensitivity are comparable to liver biopsy. Another study also found out that shear wave elastography is a reliable noninvasive modality for assessing liver elasticity (Popescu et al, 2019). In a study conducted on HBV patients for assessing the diagnostic value of SWE and liver biopsy, mean liver stiffness in F1, F2, F3, and F4 stage was 6.70 ± 2.65 kPa, 7.34 ± 3.84 kPa, 8.82 ± 3.24 kPa and 12.88 ± 5.25 kPa respectively (Kim and El-Serag, 2019), this was inline with the results of our study.…”
Section: Resultsmentioning
confidence: 94%
“…Can be easily executed on modified commercial US devices (if the machine is provided with adequate software) [6,14] Offers the possibility of choosing a large and adjustable ROI in real-time [14,17,20] Good applicability: practicable among patients with ascites and obesity [6,20] Excellent diagnostic accuracy for advanced fibrosis and cirrhosis [6,20] Affected by acute hepatitis, food intake, liver congestion, cholestasis, and alcohol consumption [6] Table 1. Advantages and disadvantages of noninvasive elastographic techniques.…”
Section: D-shear Wave Elastography (2d-sw)mentioning
confidence: 99%
“…This technique has the advantage of displaying a real-time color-coded map overlayed on a B-mode image. Furthermore, 2D-SWE estimates LS expressed in kPa or m/s [20,77]. It should be executed in a well-visualized area of the right hepatic lobe, clear of large vessels, ligaments, gallbladder, and the liver capsule, with the patient situated in a supine position with breathing suspension [15].…”
Section: Appraisal Of Liver Fibrosis By 2d Shear Wave Elastography In...mentioning
confidence: 99%
“…Therefore, 2D SWE is a reliable and current research method in modern radiology [12]. Number of publications and guidelines published in recent years indicates dynamics of this research Non-invasive diagnostics are safer and more acceptable to the patient, their use is increasing and the number of biopsies has been drastically reduced in some countries, especially for the routine evaluation of hepatitis B and C [8,13]. European Federation for societies for ultrasound in Medicine and Biology recommended the SWE that the last one assess the degree of liver stiffness in patients with CLD secondary to hepatitis especially hepatitis C [11].…”
Section: Introduction Introductionmentioning
confidence: 99%